INSIGHTS INTO CLINICO-MORPHOLOGICAL FEATURES AND MANAGEMENT OF CYSTIC FIBROSIS - Mioara-Florentina Trandafirescu; Angela Moloce; Carmen Ungureanu; Raluca Vasile; Maria Magdalena Leon; Alexandra Maştaleru; Elena Cojocaru (Romanian Society of Oral Rehabilitation, 2017)
Mucoviscidosis/ cystic fibrosis represents a potentially fatal disease, characterized by heterogeneous clinical features, mainly pulmonary, digestive, cardiac, but other systems may be involved. In recent years, there were constant concerns to identify the pathogenic disease mechanism. The molecular genetics techniques revealedin 1989 that cystic fibrosis comes from the defects of a single gene that decodes the cystic fibrosis transmembranar receptor (CFTR), a chloride channel that is distributed on a large scale in the membrane surfaces. CFTR is expressedby the airways epithelium, paranasal sinuses, pancreas, bowel, billiary tract, vasdeferens and sweat glands epithelia.Abnormalitiesin CFTR functioncause pulmonary infections and bronchectasis, leading to a respiratory insufficiency, pancreatic insufficiency and malabsorbtion, episodic intestinal obstructions, liver disease and male infertility.Atthe moment, a symptomatic treatment is available asrespiratory physiotherapy, antibiotic therapy, nebulization with mucolytics and bronchodilators, administration of protease inhibitors for pulmonary symptoms, administration of pancreatic enzymes substitutes and vitamins for pancreatic insufficiency. Though the survival rate of patients with cystic fibrosis has known important improvements in the last years, this disease remains a redoubtable adversary not only for the patient, but also for his family. Furthermore, the extremely complex physiological, biochemical and genetic profiles remains of maximum interest for the actual medical research.